2023
DOI: 10.1177/0976500x231175217
|View full text |Cite
|
Sign up to set email alerts
|

Food-derived Bioactive Peptides with Angiotensin-Converting Enzyme Inhibiting Effect: A Systematic Review

Abstract: Objective To describe the current scientific evidence of food-derived bioactive peptides and their angiotensin-converting enzyme inhibiting effect. Methods Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) were followed. We searched MEDLINE (through PubMed) and Science Direct databases to identify studies assessing food-derived bioactive peptides and angiotensin-converting enzyme-inhibiting effects. The evidence was organized and presented using tables and narrative synthesis. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…39 Several authors attribute the antihypertensive effectiveness of peptides to their structure, which is generally reported to be of low molecular weight and short length. 40,41 Some scholars have explored the ACE-inhibitory activity of peptide fragments obtained from tomato processing by-products fermented using Bacillus subtilis and found that peptides with molecular weights ranging from 500 to 850 Da were very active in their ACE-inhibitory activity compared with those with molecular weights ranging from 850 to 3000 Da. 42 This may be because small peptides can easily enter ACE active sites.…”
Section: Resultsmentioning
confidence: 99%
“…39 Several authors attribute the antihypertensive effectiveness of peptides to their structure, which is generally reported to be of low molecular weight and short length. 40,41 Some scholars have explored the ACE-inhibitory activity of peptide fragments obtained from tomato processing by-products fermented using Bacillus subtilis and found that peptides with molecular weights ranging from 500 to 850 Da were very active in their ACE-inhibitory activity compared with those with molecular weights ranging from 850 to 3000 Da. 42 This may be because small peptides can easily enter ACE active sites.…”
Section: Resultsmentioning
confidence: 99%